Strategy Identify of Sahabat NK to Increase The Sales Volume of NK Brand Corn Hybrid Seed in Probolinggo City - Ardian Hariyono; Suhendar Sulaeman; Liza Nora (Business Review and Case Studies, 2022)
East Java Province is the largest province as a producer of grain dry corn in Indonesia in 2020 with a harvested area of 1.19 million hectares with a total production of 5.37 million tons with an average productivity value of 4.51 tons per hectare. Therefore, this research aims to identify promotion strategies collaboration with grower champion also to develop main criteria of Sahabat NK that have prioritize recruit in the future to increase sales volume of NK brand hybrid corn seeds in Probolinggo City. The research method is qualitative by using study case approaching combine with Composite Performance Index (CPI) with 10 informants as the as the source of data. The research results that grower prefer to join face to face meeting rather than virtual meeting collaboration with grower champion for every promotion activity and need to add corn grower as well as grain trader for more increase the sales volume of NK brand hybrid corn seeds in Probolinggo City. Keywords: hybrid corn seed, CPI, grower champion, promotion strategy, case study